SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA UNTUK SISWA BERPRESTASI DENGAN MENGUNAKAN METODE WEIGHTED PRODUCT DI SMPN 2 TAWANGSARI SUKOHARJO - Muhammad Hasbi, Yohantino, Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2015)
SMPN 2 Tawangsari last few years to get the budget of the local government for scholarships for students who excel. But many of the problems that arise, for example in the determination of the data can be manipulated manually scholarship committee decided that there are differences on the target in this scholarship, and for too long in the decision to determine the eligible student achievement. SMPN 2 Tawangsari not yet have an application with a decision support method for determining scholarships to outstanding students. the purpose of this study is to make a make a decision support system application admission scholarships for outstanding students at SMP N Tawangsari Sukoharjo, the method used to scholarship acceptance is the Weighted Product, transactions are carried out the data analysis method consists of the analysis, design, implementation and testing. Results of the study is an decision support system application that can determine the priority value grantee, with the criteria of the average value of report cards, non-academic achievement, parental income figures, and the number of dependents of parents. Keywords : Decision Support Systems, Scholarships, Student achievement, Weighted Product